The Effects of Physician and Hospital Integration on Medicare Beneficiaries' Health Outcomes - Koch, Thomas G.; Wendling, Brett W.; Wilson, Nathan E. (The Review of Economics and Statistics, 2021)
We consider whether hospital acquisitions of physicians lead to improved clinical outcomes for medicare patients aged 65 and older. The analysis combines 2005–2012 Medicare fee-for-service and enrollment data with merger and physician affiliation information from the Levin Reports and SK&A, respectively. We determine the effect of acquisitions on several health outcomes: mortality, acute myocardial infarctions, acute circulatory conditions, ischemic heart disease, glaucoma, symptomatic diabetes complications, and asymptomatic diabetes complications. These outcomes represent the progression of hypertension and diabetes into worse health states. Our results indicate that hospital acquisitions of existing physician practices have little effect on the health outcomes we consider.